DESIGN AND ANALYSIS OF PROPELLER STRUCTURE ON LSU-03 AIRCRAFT WITH COMPOSITE MATERIAL - Rahmadi Nuranto, Awang
LSU-03 (LAPAN Surveillance UAV-03) propellers are made of wood material. In order to improve structural strength and obtain better mechanical properties, the propellers will be designed using composite materials. The composite material has a lighter mass structure compared to other materials which are the advantages of this material. Another advantages is having specific stiffness and strength in structural design. The propeller geometry is obtained from the propeller produced by the manufacturer and used for LSU-03 aircraft. The geometry is obtained by 3-D scanning and combined by direct measurement of original blades at various sections to obtain the airfoil profile segment at a specified distance. 3-D scan result is then processed as a CAD model (Computer Aided Design) using Solidworks software. Likewise the original blade, obtained from airfoil profile in various segments are also used as reference in making CAD model. Finally, results of both processes are combined to produce a geometry that approximates the original dimension. The maximum load of the propeller is occured during aircraft take-off with a speed of 20 m/sec at 7000 rpm. Based on this flight condition, the aerodynamic load and inertia load are calculated. Aerodynamic load is calculated using two methods: analytical method and numerical method. In the analytical method, the theory of BET (Blade Element Theory) is used. The numerical calculation using Ansys software. In the simulation of CFD, two types of simulations on meshing without prism mode, and for the second performed on meshing with prism mode on the surface of the propeller. The results of both methods show a fairly close result, the difference in thrust value is only 1.2% and 4.1% for both types of mesh. So the CFD simulation of aerodynamic load distribution along the surface of the blade is considered valid and ready to be used in designing the propeller structure. The aerodynamic load of CFD results can be directly imported into a Finite Element Methode / FEM analysis with Direct Import CDF / One-Way Fluid Structure Interaction (FSI) mode using Ansys Workbench software. Inertial loads are carried out numerical calculation / FEM for all material, that is white oak wood, aluminum alloy and composite. The design of the LSU-03 propeller composite structure uses a laminate composite design approad. In designing of composite structures, there are differences compared to metal materials because composites have different characteristics. This study aims to design and analyze the structure strength of the propeller (stress analysis) with carbon fiber laminate composite material by determining the type of composite material, fiber direction, fiber thickness and stacking sequence. The design configuration of the composite laminate structure of the carbon fiber propellers implements the symmetry shape on the top of the airfoil and under the airfoil so that the stacking sequence becomes [± 45/0 / ± 45), for an angle ± 45? using an Epoxy Carbon Woven composite material of 0.2 mm along the blades and angles 0? using an Epoxy Carbon UD composite material having different thicknesses along the blades as follows 3 mm thickness for the shaft, 2 mm for a radius of 100 mm, 1 mm for radius of 100 mm - 160 mm and 0.4 mm for radius 160 mm - 300 mm. Stress analysis uses Ansys Workbench software. The result obtained are the stress and deflection that occurs along the blade of the propeller. Failure criteria for wood and aluminum material are using Equivalent (Von-Mises) Stress and Maximum Principal Stress. For composite material uses Tsai-Hill failure criteria. During numerical simulation, convergence test is used to determine the convergent mesh size to produce a fixed value. Convergence test is done as much as 15 times the simulation starts from small to large the number of nodes and elements.